Molecular epidemiology of enterically colonizing Escherichia coli with resistance against third-generation cephalosporins isolated from stool samples of European soldiers with concomitant diarrhea on deployment in Western African Mali - Hoffmann, Katharina; Riediger, Matthias; Tersteegen, Aljoscha; Marquardt, Pauline; Kahlfuß, Sascha; Kaasch, Achim J.; Hagen, Ralf Matthias; Frickmann, Hagen; Zautner, Andreas E. (Frontiers in Microbiology, 2023)
Extended spectrum beta-lactamases (ESBL) are frequently found in Enterobacterales isolates from Western Africa. However, information on the molecular epidemiology of regional ESBL-positive Enterobacterales strains is scarce. In order to provide epidemiological information, ESBL-positive Escherichia coli isolates from stool samples of European soldiers with diarrhea deployed to a field camp in Mali were subjected to whole genome sequencing (Illumina MiSeq & Oxford Nanopore MinION) and antimicrobial susceptibility testing. With two exemptions, sequence-based analysis suggested an absence of transmission events between soldiers as indicated by a high genetic diversity of isolates and sequence types, confirming previous rep-PCR results. Third-generation cephalosporin resistance was associated with the presence of blaCTX-M-15 genes with (n = 14) and without (n = 5) co-occurring blaTEM-1b genes. Between 0 and 6 virulence and resistance plasmids per isolate were recorded. The detected resistance plasmids could be categorized into five types, which in turn share different sequence-identical segments, representing particular antimicrobial resistance gene-associated mobile genetic elements (MGEs). Phenotypic resistance rates within the 19 assessed isolates that showed distinguishable colony morphologies were 94.7% (18/19) against ampicillin-sulbactam and trimethoprim/sulfamethoxazole, 68.4% (13/19) against moxifloxacin, 31.6% (6/19) against ciprofloxacin, 42.1% (8/19) against gentamicin, 31.6% (6/19) against tobramycin, and 21.1% (4/19) against piperacillin-tazobactam and fosfomycin. Virulence associated genes mediating infectious gastroenteritis were rarely detected. The gene aggR, which is characteristic for enteroaggregative E. coli, was only detected in one single isolate. In summary, we found a variety of different strains and clonal lineages of ESBL-carrying E. coli. Transmission between soldiers was demonstrated in two cases and played only a minor role in this military field camp, while there were indications that resistance gene bearing MGEs had been exchanged between antimicrobial resistance gene-(ARG-)carrying plasmids.